Great education. Montesino and Caceres, Pedro Pablo (Journal of Parents and Teachers, 2012)
Fuentelcarnero (Zamora), June the 29th , 1781-Madrid, December 15 de1849.Nació within a wealthy family of Old Christians superioresen Zamorano and attended the universities of Salamanca and Valladolid, host, the latter, in which he obtained the degree of Bachelor of Medicine in 1806. circulating porentonces liberal spirit in college Helmántica retail soaked him so that was one of his trademarks identidadhasta his death.
Keywords: History of education; Leading names in education; education.